A study on the relationship between role conflict, work stress, and quality of life: Moderating effect of personal leisure participation: The case of immigration officers - Lee, Jui-Sheng; Kao, Rui-Hsin (IJRDO - Journal of Social Science and Humanities Research, 2017)
This study was undertaken to investigate the relationship between role conflict, work stress, and quality of life with immigration officers (IOs) as the research sample. The moderating effect of personal leisure participation was also explored. A total of 252 questionnaires were collected, of which 231 are valid. Of the 231 valid questionnaires, 179 came from males and 52 came from females. It was found that there is positive significant relationship for role conflict and work stress as well as work stress and quality of life. It was also found that personal leisure participation has moderating effect on the relationship between work stress and quality of life. Besides, it was also discovered that if IOs participate in leisure activities, especially the cultural activities and sports, then the negative effect of work stress would be reduced. In general, this study supplements the insufficient study about the work stress of immigration officers caused by role conflict, which may also cause a decrease in quality of life. Therefore, this article can be the practical reference for the strategy of relieving the role conflict of immigration officers, and the  leisure of the immigration officers is important in order to reduce the negative effect caused by work stress.